Strategi Pengembangan Industri Keramik di Kabupaten Purwakarta dalam Perluasan Ekspor - Shofira Ainun Rahmah; Ria Haryatiningsih (Bandung Conference Series: Economics Studies, 2023)
Abstract. The ceramic industry is one of the leading products of Purwakarta Regency. The ceramic industry in Purwakarta Regency is facing challenges in export production which has decreased due to the Covid-19 pandemic that hit causing economic sluggishness in the ceramic industry. To develop the ceramic industry in Purwakarta Regency, it is necessary to know the strengths, opportunities, aspirations and expected results and find the right strategy in dealing with these problems. The research method used in this research is descriptive of the quality of tatif. The research analysis used is SOAR (Strength, Opportunities, Aspirations, Results). The data used are primary and secondary data. The results of the research obtained that became the strength of the Purwakarta Regency Ceramics Industry were the establishment of UPTD Ceramics Research and Development, the reason was the existence of good infrastructure, aaspiration was the existence of training to improve the skills of craftsmen on an ongoing basis andthat became the desired result namely the increase in exports of Purwakarta ceramics, the increase in income of Purwakarta ceramics business actors and the expansion of export markets abroad. Themost optimal strategy for the development of the ceramic industry in Purwakarta Regency towards the export market is the Strengths-Result (SR) strategy. Where this strategy emphasizes improving product quality and human resource quality in order to increase export demand and income of business actors and the government provides convenience in terms of licensing so that ceramic production can expand abroad and also create business opportunities and income. Abstrak. Industri keramik merupakan salah satu produk unggulan Kabupaten Purwakarta. Industri keramik di Kabupaten Purwakarta menghadapi tantangan dalam produksi ekspor yang mengalami penurunan yang disebabkan oleh pandemi Covid-19 yang melanda menyebabkan kelesuan ekonomi di industri keramik. Untuk mengembangkan industri keramik di Kabupaten Purwakarta maka perlu mengetahui kekuatan, peluang, aspirasi dan hasil yang diharapkan dan mencari strategi yang tepat dalam menghadapi permasalahan tersebut. Metode penelitian yang digunakan dalam pemelitian ini adalah deskriptif kuantitatif. Analisis penelitian yang digunakan adalah SOAR (Strength, Opportunities, Aspirations, Results). Data yang digunakan adalah data primer dan sekunder. Hasil penelitian yang diperoleh yang menjadi kekuatan Industri Keramik Kabupaten Purwakarta yaitu dibentuknya UPTD Penelitian dan Pengembangan Keramik, peluangnya yaitu adanya infrastruktur yang bagus, aspirasinya yaitu adanya pelatihan untuk meningkatkan keterampilan pengrajin secara berkelanjutan dan yang menjadi hasil yang diinginkannya yaitu adanya peningkatan ekspor keramik Purwakarta, adanya peningkatan pendapatan pelaku usaha keramik Purwakarta dan meluasnya pasar ekspor di Luar Negeri. Strategi paling optimal untuk pengembangan industri keramik Kabupaten Purwakarta menuju pasar ekspor yaitu strategi Strengths-Result (SR). Dimana strategi ini menekankan pada peningkatan kualitas produk dan kualitas SDM agar terjadi peningkatan permintaan ekspor dan pendapatan pelaku usaha dan pemerintah memberikan kemudahan dalam hal perizinan sehingga produksi keramik dapat meluas di Luar Negeri dan juga terciptanya lapangan usaha serta pendapatan.